Therapeutic Strategies Toward Lactate Dehydrogenase Within the Tumor Microenvironment of Pancreatic Cancer. Issue 10 (November 2020) - Moir, John A. G.; Long, Anna; Haugk, Beate; French, Jeremy J.; Charnley, Richard M.; Manas, Derek M.; Wedge, Steve R.; Mann, Jelena; Robinson, Stuart M.; White, Steve A.
Abstract : Objectives: Pancreatic stellate cells (PSCs) play a key metabolic role within the tumor microenvironment (stroma) of pancreatic ductal adenocarcinoma (PDAC), being glycolytic and associated with protumorigenic acidification from excess lactate. This study investigates the clinical significance of glycolytic enzyme lactate dehydrogenase (LDH) and determines efficacy of the novel pan-LDH inhibitor Galloflavin. Methods: An in vitro Transwell system was adopted for coculture of PSCs and 3 PDAC cell lines (MIA PaCa-2, PANC-1, and BxPC-3). Cells were treated with Galloflavin, and outcomes were analyzed regarding proliferation, apoptosis, lactate production, and glycolytic enzyme protein expression. Immunohistochemical staining for lactate dehydrogenase B (LDHB) was performed on 59 resected PDAC tumors annotated for clinical outcome. Results: Galloflavin reduced PDAC proliferation in monoculture ( P < 0.01); however, in co-culture with PSCs, an antiproliferative effect was only evident in PANC-1 ( P = 0.001). An apoptotic effect was observed in MIA PaCa-2 and BxPC-3 in coculture ( P < 0.05). A reduction in media lactate was observed in coculture ( P < 0.01) with PSCs. Immunohistochemistry revealed stromal and tumoral LDHB expression had no impact on survival. Conclusions: Galloflavin has the potential to neutralize the acidic PDAC microenvironment and thereby reduce tumor invasiveness and metastasis. Patients with lower LDHB expression are more likely to be beneficial responders.